2015
DOI: 10.1002/2014gc005634
|View full text |Cite
|
Sign up to set email alerts
|

Thermal dependency of shell growth, microstructure, and stable isotopes in laboratory‐reared Scapharca broughtonii (Mollusca: Bivalvia)

Abstract: We experimentally examined the growth, microstructure, and chemistry of shells of the bloody clam, Scapharca broughtonii (Mollusca: Bivalvia), reared at five temperatures (13, 17, 21, 25, and 298C) with a constant pCO 2 condition ($450 latm). In this species, the exterior side of the shell is characterized by a composite prismatic structure; on the interior side, it has a crossed lamellar structure on the interior surface. We previously found a negative correlation between temperature and the relative thicknes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 63 publications
2
9
0
Order By: Relevance
“…For instance, in shells of Geukensia demissa, Lutz and Clark (1984) observed a latitudinal gradient in the percentage of the granular structure in the aragonitic inner shell layer, which they attributed to a change in mean water temperature. Temperaturedependent cyclical changes in the structural organization have also been reported for shells of Scapharca (5Anadara) broughtoni (Nishida et al, 2012(Nishida et al, , 2015. These studies show that the relative thickness of the composite prismatic layer (equivalent to OSL% in the present study) deposited during colder seasons is greater compared to those in shell portions formed during summer.…”
Section: 1002/2017gc007239supporting
confidence: 78%
See 1 more Smart Citation
“…For instance, in shells of Geukensia demissa, Lutz and Clark (1984) observed a latitudinal gradient in the percentage of the granular structure in the aragonitic inner shell layer, which they attributed to a change in mean water temperature. Temperaturedependent cyclical changes in the structural organization have also been reported for shells of Scapharca (5Anadara) broughtoni (Nishida et al, 2012(Nishida et al, , 2015. These studies show that the relative thickness of the composite prismatic layer (equivalent to OSL% in the present study) deposited during colder seasons is greater compared to those in shell portions formed during summer.…”
Section: 1002/2017gc007239supporting
confidence: 78%
“…Some of the environmentally induced structural variations can also occur without changes in the shell mineralogy (Milano et al, 2017b). Temperaturedependent cyclical changes in the structural organization have also been reported for shells of Scapharca (5Anadara) broughtoni (Nishida et al, 2012(Nishida et al, , 2015. Temperaturedependent cyclical changes in the structural organization have also been reported for shells of Scapharca (5Anadara) broughtoni (Nishida et al, 2012(Nishida et al, , 2015.…”
Section: 1002/2017gc007239mentioning
confidence: 77%
“…The seasonal and vertical migration of squid species has been described in the literatures (Bazzino et al, 2010;Argüelles et al, 2012;Yamaguchi et al, 2019); this behavior was also observed in our study. Interpreting time-series data in squids is generally more difficult than interpreting data obtained from bivalves (e.g., Nakashima et al, 2004;Owen et al, 2008;Nishida et al, 2015) because the squid species move freely, unlike bivalves. We converted the measured statolith δ 18 O values to the deduced temperature and cross-matched them with the seasonal and depth changes in the seawater temperatures to estimate the probability of the geographical distribution of S. lessoniana by using a procedure derived from a widely used method to study fish migration (involving the use of otolith δ 18 O values; Thorrold et al, 1997;Weidel et al, 2007;Shiao et al, 2014).…”
Section: Prediction Of Ontogenetic Movement and Geographical Distribumentioning
confidence: 99%
“…19.1), with the composite prismatic structure being thicker at lower water temperatures (Nishida et al 2012). Nishida et al (2015) observed shell microstructures in cultured specimens of S. broughtonii reared at five different temperatures, demonstrating experimentally the thermal dependency of the mode of shell microstructural formation in this species. Cyclical changes in microstructures with ontogeny have been observed in the subfamily Anadarinae (Mollusca: Bivalvia, Arcidae), including fossil taxa (Kobayashi and Kamiya 1968;Kobayashi 1976aKobayashi , 1976bNishida et al 2012), and can be useful for age determination and temperature reconstruction.…”
Section: Introductionmentioning
confidence: 73%
“…Thus, low temperatures below 12 °C are suggested to play a key role in the longevity and shell size in S. broughtonii. Nishida et al (2015) suggested that the faster growth at lower temperatures is achieved by dominantly building the composite prismatic structure, probably as an adaptive strategy to precipitate shells under cold water environments. However, as the composite prismatic structure is physically weaker than the crossed lamellar structure (Taylor and Layman 1972;Currey 1976), it is disadvantageous for maintaining the shell mechanical strength.…”
Section: Discussionmentioning
confidence: 99%